PENERAPAN MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN - Putri Azizah Istigfari; Ari Suriani; Yesni Yenti; Elfia Sukma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was a Classroom Action Research (CAR) using qualitative and quantitative approaches. The research was conducted in two cycles, namely Cycle I consisting of two meetings and Cycle II consisting of one meeting. Each cycle included the stages of planning, implementation, observation, and reflection. The research instruments used were observation sheets, tests, and documentation. The subjects of this study were the teacher and 22 fourth grade students of SDN 13 Pasar Remaja, Sawahlunto City.The results of the study showed improvements in lesson planning, implementation, and students’ reading comprehension learning outcomes. The lesson plan assessment increased from Cycle I and reached 96% with a Very Good qualification in Cycle II. Teacher activities improved to 90% with a Good qualification, while student activities increased to 85% with a Good qualification. Students’ reading comprehension learning outcomes also improved from an average score of 75.5 in Cycle I to 86 in Cycle II, with the learning mastery percentage reaching 90%. Therefore, the implementation of the Cooperative Learning model type Think Pair Share (TPS) was able to improve the reading comprehension skills of fourth-grade students at SDN 13 Pasar Remaja, Sawahlunto City.